Understanding vaccine hesitancy in polio eradication in northern Nigeria. Issue 47 (7th November 2017) - Taylor, Sebastian; Khan, Mahmud; Muhammad, Ado; Akpala, Okey; van Strien, Marit; Morry, Chris; Feek, Warren; Ogden, Ellyn
Abstract: Background: Vaccine hesitancy constitutes a major threat to the Global Polio Eradication Initiative (GPEI), and to further expansion of routine immunisation. Understanding hesitancy, leading in some cases to refusal, is vital to the success of GPEI. Re-emergence of circulating wild poliovirus in northern Nigeria in mid-2016, after 24 months polio-free, gives urgency to this. But it is equally important to protect and sustain the global gains available through routine immunisation in a time of rising scepticism and potential rejection of specific vaccines or immunisation more generally. Methods and findings: This study is based on a purposive sampling survey of 1653 households in high- and low-performing rural, semiurban and urban areas of three high-risk states of northern Nigeria in 2013–14 (Sokoto, Kano and Bauchi). The survey sought to understand factors at household and community level associated with propensity to refuse polio vaccine. Wealth, female education and knowledge of vaccines were associated with lower propensity to refuse oral polio vaccine (OPV) among rural households. But higher risk of refusal among wealthier, more literate urban household rendered these findings ambiguous. Ethnic and religious identity did not appear to be associated with risk of OPV refusal. Risk of vaccine refusal was highly clustered among households within a small sub-group of sampled settlements. Contrary to expectations, households in these settlements reported higher levels of expectation of government as service provider, but at the same time lesser confidence in the efficacy of their relations with government. Conclusions: Results suggest that strategies to address the micro-political dimension of vaccination – expanding community-level engagement, strengthening the role of local government in public health, and enhancing public participation of women – should be effective in reducing non-compliance, as an important set of strategies complementary to conventional didactic/educational approaches and working through religious and traditional 'influencers'.